836 DIEP Flap Monitoring Adherence. (12th October 2021) - Muscat, E; Thomson, R; Ghattaura, A
Abstract: Aim: The popularity of Deep Epigastric Perforator (DIEP) free flaps for breast reconstruction after mastectomies have increased due to their natural aesthetic results and reliability. Free flaps require strict post-operative monitoring by nursing staff during the early post-operative period where they should notify the surgeons to anticipate vascular compromise in order to salvage the flap. To ensure success the DIEP guidelines were introduced to Morriston Hospital, Swansea. This was a first cycle closed loop re-audit. Method: Interventions from initial audit were implemented in 2018. Retrospective analysis of patient notes over an 8-month period (August 2019- March 2020) and compared with DIEP checklist. Clinical notes, nursing cartex and flap observations and medication charts were reviewed. Results: 100% had bear huggers, antiemetics (87% in 2018), correct thromboprophylaxis (75% in 2018) and laxatives (37% in 2018). 100% had senior reviews daily post op (75% in 2018) . 100% had flap observations performed as guidelines immediately post op. Day1- 100% seen by pain team, 100% post op bloods performed and documented. 85% sat in the chair. Day2- 100% 1 breast drain removed (87.5% in 2018). Day3- 100% 1 abdominal drain removed (100% in 2018). Day4- 100% final abdominal drain removed (62% in 2018). and 85% discharged from hospital (50% in 2018). 100% patient followed up as per guidelines. Conclusions: This was a successful re-audit showing significant improvements in adherence rates amongst the surgical and nursing staff in the plastic surgery department. Implementation of the DIEP operation note template may help maintain such adherence amongst staff.